PENINGKATAN PENGETAHUAN MENGENAI DETEKSI BORAKS DALAM BAHAN PANGAN MENGGUNAKAN BAHAN ALAMI DI PAUD BUNAYYA ICBB BANTUL - Arviani (ABDIMAS Madani, 2019)
Food additives (BTP) are substances commonly used in processing food ingredients such as coloring, flavoring, developers, sweeteners, and preservatives. The purpose of the addition is to provide flavor, aroma, attractive appearance and food ingredients that are not easily damaged and last longer. Borax is one of the food additives that can improve the elasticity and good texture of food. Consumption of food containing borax continuously will have a negative impact on health. Therefore, borax is prohibited from being used as food additives. There are many studies that showed detection of borax uses extracts from natural product. Detection of borax can use hibiscus flower extract, turmeric, and infused water of peel of dragon fruit. This counseling aims to provide education detection of borax by using inexpensive materials, easy, and simple equipment. The results showed the participants were very enthusiastic about the subject that presented and received information about detection of borax in food in an easy, inexpensive and simple way.